2020
DOI: 10.1101/2020.09.10.291955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A visual pathway for skylight polarization processing inDrosophila

Abstract: SUMMARYMany insects use patterns of polarized light in the sky to orient and navigate. Here we functionally characterize neural circuitry in the fruit fly, Drosophila melanogaster, that conveys polarized light signals from the eye to the central complex, a brain region essential for the fly’s sense of direction. Neurons tuned to the angle of polarization of ultraviolet light are found throughout the anterior visual pathway, connecting the optic lobes with the central complex via the anterior optic tubercle and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 111 publications
(169 reference statements)
2
32
0
Order By: Relevance
“…In other insects, some AOTU-projecting medullar columnar neurons (MeTus) are known to be tuned to polarized light e-vector orientations (Heinze, 2014), and such information is known to be present in the Drosophila medulla as well (Weir et al, 2016). A more recent study has confirmed that some classes of fly AOTU neurons, as well as their downstream partners, respond to polarized light stimuli much like in other insects (Hardcastle et al, 2020). We believe TuBu01 and TuBu06 neuron types are tuned to polarized light based both on their connectivity in the BU and on their arborization patterns in the AOTU ( Figure 6C, Dii, Figure 7D), but other types may also carry information about e-vector orientation.…”
Section: Assessing the Relative Importance Of Different Synaptic Inputsmentioning
confidence: 90%
See 4 more Smart Citations
“…In other insects, some AOTU-projecting medullar columnar neurons (MeTus) are known to be tuned to polarized light e-vector orientations (Heinze, 2014), and such information is known to be present in the Drosophila medulla as well (Weir et al, 2016). A more recent study has confirmed that some classes of fly AOTU neurons, as well as their downstream partners, respond to polarized light stimuli much like in other insects (Hardcastle et al, 2020). We believe TuBu01 and TuBu06 neuron types are tuned to polarized light based both on their connectivity in the BU and on their arborization patterns in the AOTU ( Figure 6C, Dii, Figure 7D), but other types may also carry information about e-vector orientation.…”
Section: Assessing the Relative Importance Of Different Synaptic Inputsmentioning
confidence: 90%
“…A particularly strong contrast can be observed between the mapping of TuBu01 to ER4m, which is strictly one-to-one, preserving receptive fields (but not polarotopy (Hardcastle et al, 2020)), and TuBu06 to ER5, where multiple TuBu06 neurons contact a single ER5 neuron and single TuBu06 neurons project to multiple ER5 neurons ( Figure 7D,E, Figure 7-figure supplement 1B,C). This is noteworthy, as TuBu01 and TuBu06 receive input in the same region of the AOTU, but their downstream partners, ER4m and ER5 neurons, are known to have different functions: ER4m is tuned to polarized light (Hardcastle et al, 2020) and likely involved in visual orientation whereas ER5 neurons are involved in sleep (both will be discussed in more detail in later sections).…”
Section: Assessing the Relative Importance Of Different Synaptic Inputsmentioning
confidence: 96%
See 3 more Smart Citations